Exploring issues and challenges in open and distance learning (odl): framework to mitigate dropout risk among UiTM students - Ahmad Uzir, Nora’ayu; Abdul Aziz, Muhammad; Izham, Nur Izzuddin; Khairuddin, Irni Eliana; Zaini, Muhamad Khairulnizam (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
This research study aims to explore the factors that contribute to the dropout risk in an Open and Distance Learning (ODL) setting and, thus, develop a framework to mitigate this risk, particularly among Universiti Teknologi MARA (UiTM) students. As such, research objective one investigates the factors that contribute to the dropout risk in the ODL setting. Through qualitative interviews, this study has gathered in-depth insights into the personal, academic, socio-economic, and institutional factors that influence dropout decisions. Research objective two focuses on developing a framework to mitigate dropout risk among UiTM students in the ODL setting. Building upon the findings from research objective one, the framework was designed to address the identified factors and provide practical approaches to enhance student motivation and support. The findings of this research will contribute to the existing literature on dropout risk in ODL settings, providing insights into the unique challenges faced by UiTM students. The developed framework will serve as a practical tool for UiTM and other institutions to implement strategies aimed at reducing dropout rates and improving student retention in ODL programs. Ultimately, this study seeks to enhance the overall learning experience and success of UiTM students in the ODL environment.